ABAB-type phthalocyanines simultaneously bearing electron donating and electron accepting groups. Synthesis, spectroscopy, and structure. Issue 9 (15th July 2016) - Cao, Wei; Wang, Kang; Ledoux-Rak, Isabelle; Jiang, Jianzhuang
Abstract : Mg( trans -TPTCPc) was successfully prepared and structurally characterized, representing the first structurally characterized ABAB-type phthalocyanine compound simultaneously bearing electron-donating and electron-accepting groups. Abstract : The ABAB-type 1, 4, 15, 18-tetrapentyloxy-8, 11, 22, 25-tetrachlorophthalocyaninato magnesium compound Mg( trans -TPTCPc) (1 ) was successfully isolated from the mixed cyclic tetramerization of 4, 7-bis(pentyloxy)-1, 3-diiminoisoindoline as precursor A, actually the 1, 3-diiminoisoindoline form of 3, 6-bis(pentyloxy)-1, 2-benzenedinitrile, and 4, 5-dichlorophthalonitrile as precursor B in refluxing pentanol in the presence of magnesium pentoxide in a relatively good yield of 6.2%. Its molecular structure was clearly revealed on the basis of single crystal X-ray diffraction analysis, representing the first structurally characterized ABAB-type phthalocyanine compound, simultaneously bearing electron-donating pentyloxy groups and electron-accepting chloro substituents. Nevertheless, with1 as the starting material, the corresponding sandwich-type bis(phthalocyaninato) lutetium double-decker complex Lu III ( trans -TPTCPc)2 (2 ) was also prepared and structurally characterized, showing a high hyperpolarizability of 1240 × 10 −30 esu as determined by harmonic light scattering (HLS), indicating the great potential of these kinds of phthalocyanine compounds in the field of second-order NLO materials.